POLITIK HUKUM PIDANA MATI DALAM SISTEM HUKUM PIDANA NASIONAL - Andi Desmon; Yenni Fitria; Rina Rahma Ornella Angelia (Ensiklopedia Research and Community Service Review, 2026)
Abstract: The regulation of the death penalty as a special punishment that is always imposed alternatively, as articulated in the National Criminal Code (KUHP), represents an effort toward the abolition of capital punishment. This is because alternative capital punishment can be commuted to life imprisonment or 20 (twenty) years of imprisonment, provided that the requirements set forth in the National Criminal Code are met. The implementation of a 10 (ten) year probationary period provides the convict with an opportunity to reform, with the expectation that the death sentence may be converted into life imprisonment or 20 (twenty) years of imprisonment. Capital punishment with a probationary period can be regarded as a middle ground to maintain a balance between retentionist and abolitionist views. Keywords: Legal Policy, Criminal Law, Death Penalty.